Pengaruh Word Of Mouth, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian (Studi pada Konsumen UMKM Keripik Samiler Alita Di Kabupaten Malang) - Farida, Rizki Ayu; Mahsuni, Abdul Wahid; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the relationship between the influence of word of mouth, price, and product quality on purchasing decisions at MSMEs Samiler Alita Chips. This research uses a case study on consumers of MSMEs Samiler Alita Chips where data is obtained by distributing questionnaires via g-form to consumers of MSMEs Samiler Alita chips which are selected by random sampling. Determining the number of samples in this study using the Malhotra formula and the results obtained were 100 respondents. The data analysis method used in this study is data processing using the IBM SPSS 26 program. The results of this study indicate that the effect of word of mouth, price, and product quality simultaneously affects purchasing decisions. Word of mouth partially has no effect on purchasing decisions, price partially affects purchasing decisions, product quality partially affects purchasing decisions. Keywords: Word of Mouth, Price, Product Quality, Purchasing Decisions